'What is wrong with men?': revisiting violence against women in conflict and peacebuilding. (3rd May 2016) - Pankhurst, Donna
Abstract: Much has been written about the high rates of rape and other forms of violence against 'enemy' women in wartime and sustained violence against women in post-war contexts. Research on violence against women, recognised as a problem for peace and development and even a threat to international security, has begun to identify and explain contrasts between different locations. The explanations focus on men, their behaviour and 'masculinities', some of which, and even some military codes, may even proscribe such violence. By contrast, research on the mental health of male former combatants, and possibly other male survivors of war trauma, suggests that there is a strong risk of them perpetrating violence specifically against women, even in cases where the highest standard of veteran care is expected, but without much explanation. This article considers what potential there is in this topic for lessons in peacebuilding policy and identifies areas for future research.